Anatomic Reconstruction of Distal Radioulnar Ligaments With Tendon Graft for Treating Distal Radioulnar Joint Instability: Surgical Technique and Outcome. Issue 3 (September 2017) - Meyer, Daniela; Schweizer, Andreas; Nagy, Ladislav
Abstract : Among the various reasons for chronic posttraumatic ulnar-sided wrist pain, instability of the distal radioulnar joint (DRUJ) has recently received major attention and finally achieved fundamental progress in understanding thanks to anatomic and biomechanical studies. This has resulted in more physiological and successful treatment methods compared with the historic options. One and the most dramatic surgical technique consists in the replacement of the main ligamentous stabilizer of the DRUJ, the so-called triangular fibrocartilage, with a tendon graft. On the basis of our experience, the refined surgical technique is presented as well as the results obtained in a retrospective consecutive case series of 48 patients with 48 wrists followed-up for 16 months in average (6 to 43) clinically and radiographically. Out of 48 unstable DRUJ's stability was restored in 44 patients associated with a significant pain relief by 1.44 points (on a scale 0 to 4). There was however a loss of forearm rotation of 20 degrees in average (pronation—8 degrees; supination—12 degrees), whereas the range of motion of the wrist and grip strength remained unchanged. We did not find any influence on the result by performing simultaneous ulnar shortening osteotomy, the duration of cast immobilization or the positioning in the cast. There were no postoperative complications, 4 failed cases needed secondary procedures (2× rereconstruction, 2× Sauvé-Kapandji-operation).